How does Indonesian Secondary-ELT Textbook Shape Environmental Consciousness? An Ecocritical Discourse Analysis - Basya, Dihliza; Maulidia, Belqis Azida (Proceedings of English Linguistics and Literature, 2024)
In numerous studies conducted worldwide researchers, academics, and educators have been drawn to the environmental values present in English Language Teaching (ELT) textbooks. Nevertheless, there is a scarcity of literature that examines the environmental values of EFL textbook, particularly in Indonesia. This study employs Eco-Critical Discourse Analysis (ECDA) to scrutinize the representation of environmental issues in ELT textbooks for secondary school affect Indonesian students’ environmental awareness. The verbal data was analysed using Halliday’s Systemic Functional Analysis. Kress and Van Leeuwen’s Visual Grammar Theory was implemented to explore, comprehend, and investigate visual representations from selected ELT Textbook. This investigation assists in the development of ELT textbook that is consistent with environmental education principles. It is regarded necessary to conduct additional educational on environmental issues in Indonesian ELT textbooks that are used in the majority of Secondary Schools in order to foster a greater understanding of the application of environmental awareness principles in the ELT context.